2017
DOI: 10.21767/2574-2825.100011
|View full text |Cite
|
Sign up to set email alerts
|

'The Relationship Between Post-Traumatic Stress Disorder and Coping Strategies among Patients with Cancer in Gaza Strip

Abstract: Aim: The study aimed to examine the mental health status of the patients with cancer and the coping strategies that adopted by them in front of stressful situations. Method:The sample consisted of 358 patients with cancer in the oncology clinic at Shifa Hospital in Gaza Strip. Participants were interviewed individually by questionnaire include socioeconomic questionnaire, PTSD scale, and Ways of coping Scale. Results:The study showed that 42.5% of patients had PTSD, 47% had re-experiencing of PTSD, 40.5% had h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…These results are in agreement with those observed in earlier studies [8]. While, a recent study showed that wish and avoidance thinking was mostly used (69.0%) in Gaza patients with cancer to deal with stressful situations [33]. The most important aspects of coping with breast cancer in Iranian women at both steps were spiritual coping strategy.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with those observed in earlier studies [8]. While, a recent study showed that wish and avoidance thinking was mostly used (69.0%) in Gaza patients with cancer to deal with stressful situations [33]. The most important aspects of coping with breast cancer in Iranian women at both steps were spiritual coping strategy.…”
Section: Discussionsupporting
confidence: 92%
“…Symptoms must last at least 1 month and cause significant impairment in functioning. Many studies have found that diagnosing with cancer could trigger PTSS (Andrykowski et al, 1998; Al Jadili and Thabet, 2017). These symptoms will further negatively affect patients’ QoL (Ha et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The results different with results of Lubbad et al [23] revealed the most common reported anxiety symptoms were; I would like to be happy like others 92.1%; I lost my sleep because of anxiety 86.7%; while the lowest items were; I feel no redness face at all 22.2%; I feel quietness all times 26.3%. However, Al-Jadili et al [3] revealed that state anxiety was at the highest rank 60.8%, followed by trait anxiety 54.6% among the cancer patients. Where, Karabulutlu et al [11] in his study revealed that anxiety was determined in 61.5% of the cancer patients.…”
Section: Discussionmentioning
confidence: 96%
“…Breast cancer is the highest among females and focus in the age group between 20-59, where colon cancer ranked second, with (236) reported cases and (10.8%) from all reported cancers (MOH,higher levels of cancer-related posttraumatic stress symptoms than Danish women with comparable disease severity [2]. Furthermore, the stressors of the cancer patients at Shifa hospital where state anxiety was at the highest rank 60.8%, followed by trait anxiety 54.6%; re-experiencing PTSD at the third rank 47.0%, PTSD 42.5%, hyper-arousal 40.5%, avoidance 40.1% [3]. There are many stressors that face women diagnosed with cancer, including the fear of possible death, stress of informing family members, and the stress associated with being informed that their lives is going to be drastically change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation